(untitled) (Cadernos de Sociomuseologia, 2025)
The text here presented is at the crossroads of three people (Mãe Nilce de Iansã, Maria Helena Versiani and Mario Chagas) and addresses the fight against religious racism based on the case study of Acervo Nosso Sagrado (Our Sacred Collection) which arrived at the Museu da República (Museum of the Republic) on September 21, 2020. The text stems from a dialogue with the ancestors and it confronts the distinction between combating intolerance and combating religious racism. Our analysis recognises that the transfer of Nosso Sagrado (Our Sacred) to the Museu da República (Museum of the Republic) implied the establishment of a Shared Stewardship Group for the care of the collection; finally, the text reflects on the expression ‘Our Sacred’ and its conceptual subtleties. KEYWORDS: Nosso Sagrado (Our Sacred); Religious Racism; Museu da República (Museum of the Republic); Social Museology; Shared Stewardship.